Pentamethinium salts as ligands for cancer: Sulfated polysaccharide co-receptors as possible therapeutic target - Bříza, Tomáš; Králová, Jarmila; Rimpelová, Silvie; Havlík, Martin; Kaplánek, Robert; Kejík, Zdeněk; Martásek, Pavel; Mikula, Ivan; Džubák, Petr; Hajdúch, Marián; Ruml, Tomáš; Král, Vladimír (Bioorganic chemistry, 2019)
A series of pentamethinium salts with benzothiazolium and indolium side units comprising one or two positive charges were designed and synthesized to determine the relationships among the molecular structure, charge density, affinity to sulfated polysaccharides, and biological activity. Firstly, it was found that the affinity of the pentamethinium salts to sulfated polysaccharides correlated with their biological activity. Secondly, the side heteroaromates displayed a strong effect on the cytotoxicity and selectivity towards cancer cells. Finally, doubly charged pentamethinium salts possessing benzothiazolium side units exhibited remarkably high efficacy against a taxol-resistant cancer cell line.
Keywords: molekulární struktura; Animals; Humans; nádorové buněčné linie; estery kyseliny sírové; protinádorové látky; CHO buňky; benzothiazoly; Hydrophobic and Hydrophilic Interactions; lidé; zvířata; Sulfuric Acid Esters; glykosaminoglykany; Ligands; racionální návrh léčiv; ligandy; Antineoplastic Agents; Pyridinium Compounds; pyridinové sloučeniny; Benzothiazoles; Apoptosis; hydrofobní a hydrofilní interakce; apoptóza; Molecular Structure; CHO Cells; Cricetulus; Drug Design; Glycosaminoglycans; Indoles; Cell Line, Tumor; indoly